The identities of Nemophora augites (Meyrick, 1938) and Nemophora amatella (Staudinger, 1892): correction of misidentifications and description of a new species (Lepidoptera: Adelidae) from China - Kozlov, Mikhail V. (Zootaxa, 2023)
This study corrects misidentifications found in a recently published paper by Sun, Wang & Li (2022; Zootaxa 5219, 301–338). These authors used the name ‛Nemophora amatella (Staudinger, 1892)’ for N. augites (Meyrick, 1938) and the name ‛N. augites (Caradja et Meyrick, 1938)’ for an undescribed species. To resolve these problems, I set aside the earlier (erroneous) lectotype fixation of N. augites (Meyrick, 1938) and replace it with a new lectotype, designate a lectotype of N. amatella (Staudinger, 1892), provide differential diagnoses and morphological descriptions of these species, and describe N. yunnanica Kozlov, sp. nov. from Lijiang (Yunnan, China). The reported misidentifications show that any revision of a taxonomically challenging group like the fairy moth genus Nemophora Hoffmannsegg, 1798 should always be based on the examination of all survived primary types of previously described species.